Biotic homogenization destabilizes ecosystem functioning by decreasing spatial asynchrony. Issue 6 (30th April 2021) - Wang, Shaopeng; Loreau, Michel; de Mazancourt, Claire; Isbell, Forest; Beierkuhnlein, Carl; Connolly, John; Deutschman, Douglas H.; Doležal, Jiří; Eisenhauer, Nico; Hector, Andy; Jentsch, Anke; Kreyling, Jürgen; et al.
Abstract: Our planet is facing significant changes of biodiversity across spatial scales. Although the negative effects of local biodiversity (α diversity) loss on ecosystem stability are well documented, the consequences of biodiversity changes at larger spatial scales, in particular biotic homogenization, that is, reduced species turnover across space (β diversity), remain poorly known. Using data from 39 grassland biodiversity experiments, we examine the effects of β diversity on the stability of simulated landscapes while controlling for potentially confounding biotic and abiotic factors. Our results show that higher β diversity generates more asynchronous dynamics among local communities and thereby contributes to the stability of ecosystem productivity at larger spatial scales. We further quantify the relative contributions of α and β diversity to ecosystem stability and find a relatively stronger effect of α diversity, possibly due to the limited spatial scale of our experiments. The stabilizing effects of both α and β diversity lead to a positive diversity–stability relationship at the landscape scale. Our findings demonstrate the destabilizing effect of biotic homogenization and suggest that biodiversity should be conserved at multiple spatial scales to maintain the stability of ecosystem functions and services.